Investigating the Hand Ownership Illusion With Two Views Merged in - Okumura, Keisuke; Ora, Hiroki; Miyake, Yoshihiro (Frontiers in Robotics and AI, 2020)
Researchers investigating virtual/augmented reality have shown humans' marked adaptability, especially regarding our sense of body ownership; their cumulative findings have expanded the concept of what it means to have a body. Herein, we report the hand ownership illusion during “two views merged in.” In our experiment, participants were presented two first-person perspective views of their arm overlapped, one was the live feed from a camera and the other was a playback video of the same situation, slightly shifted toward one side. The relative visibility of these two views and synchrony of tactile stimulation were manipulated. Participants' level of embodiment was evaluated using a questionnaire and proprioceptive drift. The results show that the likelihood of embodying the virtual hand is affected by the relative visibility of the two views and synchrony of the tactile events. We observed especially strong hand ownership of the virtual hand in the context of high virtual hand visibility with synchronous tactile stimulation.